Obszary współdziałania wyższych uczelni z pracodawcami i stowarzyszeniami zawodowymi w kształceniu specjalistów = Areas of cooperation between universities in the training of specialists. Universities - employers - professional associations - Górski, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the results of the research aiming at improving education quality at universities. The starting point is to define educational objectives at universities, which according to the author are: 1) education (transfer of knowledge to students); 2) socialization (preparing students for future professional roles); 3) individual development of students (stimulating via teacher - student interaction and creating appropriate conditions for the development); 4) social change (university and teacher and student environment work to solve the problems and reconstruct social relationship).
Keywords: szkolnictwo wyższe; pracodawcy; stowarzyszenia zawodowe; współpraca